Using financial incentives to increase physical activity among employees as a strategy of workplace health promotion: protocol for a systematic review. Issue 3 (5th March 2021) - Heise, Thomas Leonhard; Frense, Jennifer; Christianson, Lara; Seuring, Till
Abstract : Introduction: Shifts towards sedentary occupations in high-income countries (HIC) over the last decades and the health burden associated with physical inactivity have led to innovative strategies to promote physical activity (PA) among the working population. Financial rewards have been proposed to incentivise participation in programmes promoting PA or the achievement of PA-related goals. This review will assess (1) effects of financial incentives provided by employers to promote PA on programme adherence/compliance, PA and closely linked outcomes (eg, days of sick leave), (2) effects according to age, gender, implementation and study quality and (3) intervention costs and cost-effectiveness. Methods and analysis: We will search for relevant studies in eight academic databases, two grey literature resources, two trial registers and on five organisational websites (oldest record/content to present). We will include (cluster) randomised controlled studies with a financial incentive to promote PA as intervention (≥1 months), conducted among employees in HIC and reporting data on at least one primary outcome in stages of screening (title/abstract, full text). To assess study quality and potential bias, we will use the revised Cochrane risk-of-bias tool (RoB 2). We will extract study data into prepiloted extraction sheets. Each task in screening, quality assessment and data extraction will be done by two authors independently. If a sufficient number of studies provide homogeneous data (ie, similar follow-up) for primary outcomes, meta-analyses will be carried out. We will report GRADE ratings to provide information on the certainty of the evidence. Ethics and dissemination: For this review, no ethical approval will be required because only data of studies in which informed consent was obtained will be considered and analysed. The final review manuscript will be published in an Open Access journal. To ensure effective promotion of this review project, we will disseminate major findings through relevant communication channels. PROSPERO registration number: CRD42020184345.